Functionalization of pine sawdust biochars with Mg/Al layered double hydroxides to enhance adsorption capacity of synthetic azo dyes: Adsorption mechanisms and reusability - Jonggu Kim; Guen-Hyeok Bak; Da-Young Yoo; Young-In Lee; Yong-Gu Lee; Kangmin Chon (Heliyon, 2023)
This study determined that the adsorption of azo dyes, Methyl Orange (MO) and Sunset Yellow FCF (SYF), using the pristine pine sawdust biochar (PSB) and post-modified PSB with Mg/Al layered double hydroxides (PSB-LDHMgAl) was examined to offer valuable information into the differences in their adsorption mechanisms. Although a lower specific surface area of PSB-LDHMgAl (147.2 m2 g−1) than PSB (495.7 m2 g−1), LDHMgAl were successfully functionalized on the PSB surface through co-precipitation, which was highly related to the improvements of adsorption capacity of PSB-LDHMgAl toward MO and SYF. The MO and SYF adsorption kinetics by PSB and PSB-LDHMgAl were confirmed to the pseudo-second-order and considered chemisorption. The adsorption capacity of MO and SYF adsorbed onto PSB-LDHMgAl (MO = 21.8 mg g−1, SYF = 23.6 mg g−1) were significantly higher than that of PSB (MO = 2.2 mg g−1, SYF = 1.6 mg g−1). The adsorption isotherms of MO and SYF by PSB were well fitted by Freundlich isotherm, whereas the MO and SYF via PSB-LDHMgAl were by Langmuir isotherm. Even after 3 adsorption-desorption cycles using desorbents, the PSB-LDHMgAl remained excellent reusability (reuse efficiency: >81.2%). These findings suggest that post-modification with LDHMgAl might accelerate the adsorption performance (i.e., electrostatic interaction) of azo dyes to PSB in water.